Joint Subcarrier and Power Allocation for Uplink Integrated Sensing and Communication System - Li, Yiheng; Wei, Zhiqing; Feng, Zhiyong (IEEE sensors journal, 2023)
Integrated sensing and communication (ISAC) supporting various emerging applications has become one of the leading technologies in sixth generation (6G) networks. This paper focuses on the uplink orthogonal frequency division multiplex (OFDM) ISAC system. With the help of multiple vehicles, the base station (BS) can collect information about its surroundings through the uplink signals. Nevertheless, the rapid growth of the communication and sensing sectors has led to a growing scarcity of spectrum resources, resulting in a tradeoff between the performance of sensing and communication subsystems. To address this challenge, our paper introduces an efficient joint subcarrier and power allocation strategy for the uplink OFDM ISAC system. The critical issue is to minimize the Cramer-Rao lower bound (CRLB) by sparsely selecting the best possible sensing subcarriers and allocating the optimal transmit power to the corresponding subcarriers while satisfying the communication data rate (CDR) requirement. The resulting optimization problem is formulated as a nonconvex problem. After convex relaxation reformulation, we adopt the cyclic minimization algorithm (CMA) to iteratively solve the subcarrier selection and power allocation problems. Finally, numerical results suggest that the proposed joint optimization strategy is more effective than traditional methods.